The lightning thief - Riordan, Rick (Riordan, Rick. Percy Jackson & the Olympians, 2022)
Twelve-year-old dyslexic Percy Jackson goes to summer camp where he sees images of Greek gods and goddesses everywhere even when no one else can. Percy learns he is the child of a famous god right in the middle of an intense battle as the gods try to topple each other.